The role of intra-regional trade in the Pacific Alliance's integration into Asia-Pacific - Mazuelos Carpio, André Alejandro (2022)
One of the objectives of the Pacific Alliance is trade integration orientated towards Asia-Pacific; However, the integration of the bloc’s members into that region’s markets is circumscribed by their low levels of intra-regional trade and their limited export diversification. On this basis, this research seeks to explain the extent to which the intra-regional trade of the Pacific Alliance affects its inclusion in the Asia-Pacific markets. The methodology research is explanatory. Indicators ofeconomic interdependence are analyzed to observe the degree of intra-regional trade within the alliance and in other Asia-Pacific regions, as well the technological content of each member’s export basket. The results show that while the Pacific Alliance’s trade has an extra-regional bias and its exports are tending towards reprimarization, this has not been an impediment to the objective of inclusion in international markets with an orientation towards Asia-Pacific as the bloc’s trade bias towards that region has increased.